Genome-Wide Association Study Identifies Genomic Loci Associated With Neurotransmitter Concentration in Cattle - Chen, Qiuming; Qu, Kaixing; Ma, Zhijie; Zhan, Jingxi; Zhang, Fengwei; Shen, Jiafei; Ning, Qingqing; Jia, Peng; Zhang, Jicai; Chen, Ningbo; Chen, Hong; Huang, Bizhi; et al. (Frontiers in Genetics, 2020)
Abnormal neurotransmitter concentration is one of the factors that affect health status, behavioral personality and welfare level of animals, but the genetic basis of the abnormality is still largely unknown. The objective of this study is to identify putative genomic loci associated with neurotransmitter concentration in cattle. We measured serotonin (5HT), dopamine (DA), cortisol, glutamate (Glu) and ACTH concentrations in blood serum using double antibody sandwich ELISA in 30 Brahman cattle and 127 Yunling cattle. Interestingly, we found ACTH concentration was positively correlated with body weight, cannon circumference and hip width (P < 0.05). Genome-wide association study (GWAS) was performed with mixed linear models using autosomal SNPs derived from whole-genome sequence. We identified five, five, two, three and five suggestive loci associated with 5HT, DA, cortisol, Glu and ACTH concentration, respectively. These 20 associated loci implicated 18 candidate genes. For Glu concentration, the most significant association locus was assigned to MCHR1, a G-coupled receptor which could modulate glutamate release. For dopamine concentration, a very strong association locus was located in the intron of SLC18A2, which is a critical mediator of dopamine dynamics. However, for ACTH concentration, a very strong association locus was assigned to HTR1F, a G-protein coupled receptor which can influence on release of ACTH. Other candidate genes of interest identified for neurotransmitter concentration were PRMT6, GADD45A, PCCA, ANGPT1, ACCS, LOC100336971, TNR, GSDMA, CNTN3, CARMIL1, CDKAL1, RBFOX1, PCDH15 and LGALS12. Our findings will provide target for genetic improvement of neurotransmitter-related traits in domestic cattle and basic materials for studying the mechanism of neurotransmitter synthesis, release and transport in human and animals.